2021
DOI: 10.1097/psy.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions in the Treatment of Obsessive-Compulsive and Related Disorders: A Systematic Review

Abstract: add state sales tax. The GST tax of 7% must be added to all orders shipped to Canada (Wolters Kluwer Health, Inc., GST Identifi cation #895524239, Publications Mail Agreement #1119672). Prices subject to change without notice. Visit us online at www.lww.com. Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can choose to purchase a print and online subscription together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Yet, cross-sectional studies have not supported a link between OCS/PRBs and exercise to date (Freedman and Richter, 2021). One single-arm exercise intervention utilising moderate intensity physical exercise showed acute but significant decreases in OCD symptoms (for a review, see Brierley et al, 2021b). Further research into the relationship between exercise with OCS and PRBs, including in the general population, is required.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, cross-sectional studies have not supported a link between OCS/PRBs and exercise to date (Freedman and Richter, 2021). One single-arm exercise intervention utilising moderate intensity physical exercise showed acute but significant decreases in OCD symptoms (for a review, see Brierley et al, 2021b). Further research into the relationship between exercise with OCS and PRBs, including in the general population, is required.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional support for patients in psychiatric care is inadequate. Research has examined the effects of nutritional supplements and deficiencies associated with mental disorders (Carnegie et al, 2020; Marx et al, 2021; Sarris, 2019), the lifestyle intervention by diet quality in psychological depression (Brierley et al, 2021), and the role of dietary interventions to prevent depression (Lassale et al, 2019). However, few studies have addressed the diets of patients in psychiatric care, and effective support methods to assist such patients and improve their QOL have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…10 Further, higher sugar and fat intake is shown to be significantly associated with greater gambling pathology, 11 while robust randomized controlled trials have shown the nutrient supplement n-acetylcysteine (commonly found in protein-rich foods) to improve symptoms across OCRDs spectrum alongside standard treatment. [12][13][14][15] While many studies have relied on cross-sectional data and we therefore cannot infer causal association between lifestyle and compulsive behaviors, causal links between diet factors and OCD-like behaviors have been shown in animal models. 16,17 Research has suggested that individuals with OCD (and without depression) present with a less varied gut microbiome and higher inflammation levels when compared to a nonpsychiatric control group.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a review of sleep in obsessive-compulsive and related disorders (OCRDs) detected a general trend of increased sleep disturbance in people experiencing OCRDs, with sleep disturbance being more common in OCD and HD [ 10 ]. Further, higher sugar and fat intake is shown to be significantly associated with greater gambling pathology [ 11 ], while robust randomised controlled trials have shown the nutrient supplement n-acetylcysteine (commonly found in protein-rich foods) to improve symptoms across OCRDs spectrum alongside standard treatment [ 12 15 ]. While many studies have relied on cross-sectional data and we therefore cannot infer causal association between lifestyle and compulsive behaviours, causal links between diet factors and OCD-like behaviours have been shown in animal models [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation